Analisis Kinerja Keuangan Terhadap Harga Saham (Studi Pada Perusahaan Food And Beverages 2017-2021) - Marvina, Evi; Idaman, Northa; Renfiana, Lilis (Budgeting: Jurnal Akuntansi Syariah, 2024)
This study aims to analyze what factors affect the stock price of Food and Beverages companies listed on the Indonesia Stock Exchange. It is known that the development of the national economy in Indonesia is assisted by the food and beverages subsector which is a mainstay industry in making a major contribution to national economic growth, with its consistently recorded performance achievements. This research uses a quantitative approach, with a clausal associative research type. In this study using the variables Return On Asset (ROA), Net profit margin (NPM), Earning per share (EPS) and stock prices of food and beverages subsectors listed on the IDX in 2017-2021. Based on the research results, Return On Assets (ROA) has no effect on share prices and results. Net profit margin (NPM) has no effect on stock prices and results. Earnings per share (EPS) has a significant positive effect on share prices. The variables Return On Assets (ROA), Net profit margin (NPM), Earnings per share (EPS) simultaneously have a significant influence on stock prices due to increased public confidence in the treatment of economic activity, thereby encouraging an increase in manufacturing activity to the point where it is in the expansive zone at the level 53.9 in November 2021 and finished goods prices are generally stable nationally.